2012
DOI: 10.1167/12.13.11
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements reset visual perception

Abstract: Human vision uses saccadic eye movements to rapidly shift the sensitive foveal portion of our retina to objects of interest. For vision to function properly amidst these ballistic eye movements, a mechanism is needed to extract discrete percepts on each fixation from the continuous stream of neural activity that spans fixations. The speed of visual parsing is crucial because human behaviors ranging from reading to driving to sports rely on rapid visual analysis. We find that a brain signal associated with movi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…The difference in the structure of functional connectivity between visual stimulation and intertrial periods across anesthesia and awake states could be attributed to the lack of saccadic eye movements in intertrial periods during anesthesia. Saccadic eye movements reset visual perception ( 38 ), and their absence could create a persistent network state, showing no reset, resulting in very similar patterns of correlations during visual stimulation and intertrial periods.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in the structure of functional connectivity between visual stimulation and intertrial periods across anesthesia and awake states could be attributed to the lack of saccadic eye movements in intertrial periods during anesthesia. Saccadic eye movements reset visual perception ( 38 ), and their absence could create a persistent network state, showing no reset, resulting in very similar patterns of correlations during visual stimulation and intertrial periods.…”
Section: Resultsmentioning
confidence: 99%
“…While previous studies have suggested that post-saccadic increases in visual neuron firing rates might reflect a window of enhanced processing of the stimuli introduced by saccades 9 13 , our finding that these firing rate increases are accompanied by decreased stimulus selectivity argues against this. If perisaccadic modulation in V1 serves to reset processing in the cortical network (such as through ‘phase-resetting' of ongoing network oscillations 4 ), such synchronized firing rate modulations may help to parse stimuli presented during separate fixations 59 , and ultimately integrate them into a seamless visual percept.…”
Section: Discussionmentioning
confidence: 99%
“…200Hz) eyetrackers with low latency may potentially allow to predict saccadelanding positions at the beginning of a saccade using a ballistic model [Komogortsev and Khan 2008]. Being able to estimate the future gaze position would then allow to perform the disparity adjustments within the time window of a saccade during which the stream of visual processing is disrupted [Paradiso et al 2012]. However, avoiding latency is a hard problem and requires that it is being traded off against a much lower accuracy in the determination of the attended depth plane.…”
Section: Discussionmentioning
confidence: 99%